Comorbid Cerebral and Pulmonary Edema at 7010 M/23000 Ft: An Extreme Altitude Perspective (Journal of Medicine, 2014)
High Altitude Cerebral Edema (HACE) and High Altitude Pulmonary Edema (HAPE) are two dreaded altitude emergencies which can independently lead to complications. Two cases of suspected comorbid HACE and HAPE were managed at 5800 m/19000 ft in Karakoram Himalayas. Altitude acclimatization, purported to prevent high altitude illness, may not be protective. Comorbid HACE and HAPE at extreme altitude may present atypically necessitating high index of suspicion and prompt clinical decision making in challenging situations. One man HAPE bag/PHC is an excellent temporary measure in cases of delayed descent/evacuation. Due attention to extreme altitude emergencies is required in view of increased recreational, scientific and military activities at extreme altitude.DOI: http://dx.doi.org/10.3329/jom.v14i2.19668 J Medicine 2013, 14(2): 153-155